2023
DOI: 10.1130/ges02508.1
|View full text |Cite
|
Sign up to set email alerts
|

Picture Gorge Basalt: Internal stratigraphy, eruptive patterns, and its importance for understanding Columbia River Basalt Group magmatism

Abstract: The Picture Gorge Basalt (PGB) of the Columbia River Basalt Group (CRBG) has been previously thought to be limited in its eruptive volume (<3000 km3) and thought to not extend far from its type locality. At present, PGB represents only 1.1 vol% of the CRBG with a relatively limited spatial distribution of ~10,000 km2. New age data illustrate that the PGB is the earliest and longest eruptive unit compared to other main-phase CRBG formations and that some dated basaltic flows reach far (~100 km) beyond th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…This phase correlates well with the later PGB (cf. [98]) and particularly well with the voluminous Grande Ronde Basalt, which is ~16.3 to 15.9 Ma. Thus, magma reservoirs hosting these mafic magmas must have been widespread in the crust below those rhyolite centers (Figure 12 and Section 4.2).…”
Section: Consequences Of Arrival Storage and Dispersal Of Columbia Ri...mentioning
confidence: 84%
See 1 more Smart Citation
“…This phase correlates well with the later PGB (cf. [98]) and particularly well with the voluminous Grande Ronde Basalt, which is ~16.3 to 15.9 Ma. Thus, magma reservoirs hosting these mafic magmas must have been widespread in the crust below those rhyolite centers (Figure 12 and Section 4.2).…”
Section: Consequences Of Arrival Storage and Dispersal Of Columbia Ri...mentioning
confidence: 84%
“…Direct stratigraphic evidence for contemporaneity of CRBG volcanism and rhyolites is within areas where CRBG units are intercalated with rhyolites. This area includes (1) the greater Malheur River Gorge area (Figure 3), where Grande Ronde Basalt is intercalated with rhyolites overlying older CRBG units (e.g., [16,70,98], and (2) peripheral areas in which units of the Dinner Creek Tuff are intercalated into Grande Ronde Basalt at Rattlesnake Road [18], north of Baker City, and along the Oregon/Idaho state border east of Baker City (Figure 3). Additionally, several other ignimbrite units emplaced farther south are intercalated with Steens Basalt [103].…”
Section: Mid-miocene Rhyolites In Context To Crbgmentioning
confidence: 99%
“…Recent work by [2] extended the PGB formation to the east (Figure 1) and yielded 40 Ar/ 39 Ar ages that indicate that eruptive activity of the Picture Gorge Basalt started significantly earlier around 17.25 Ma, making the PGB older than or, as a minimum, as old as the earliest CRBG lavas anywhere. The updated timeframe now makes it probable that the lower [2,12,24,25]; red line for ages of AB1&2 flows of this study; 'prior PGB' = stratigraphic position prior to [2], upward arrow on PGB to indicate youngest age of 15.75 Ma [24] (see text for discussion). (B) Flow stratigraphy of Imnaha Basalt after [26]; AB = American Bar, RC = Rock Creek, FC = Fall Creek, and LC = Log Creek subunits.…”
Section: Introductionmentioning
confidence: 95%
“…Its volume is 3300 km 3 and is relatively small, accounting for only 1.1% of the CRBG as compared to the other major units like the Imnaha Basalt and Grande Ronde Basalt, which comprise 15% and 72% of the CRBG, respectively [1]. However, recent work by [24] has revealed that the extent of PGB lavas is likely larger by ~14,000 km 2 with a total distribution of ~25,000 km 2 (Figure 1), yielding an additional volume ranging from ~3000-8000 km 3 based on using different thickness estimates.…”
Section: The Picture Gorge Basaltmentioning
confidence: 99%
See 1 more Smart Citation